Industry immersion learning : real-life industry case-studies in biotechnology and business - Borbye, Lisbeth (Weinheim : Blackwell-Wiley, 2009)
How to Create and Conduct Real-Life Reusable Case Studies with Industry Employer Alliances and Projects Written and Endorsed by Science and Business Professionals in the Research Triangle Park in North Carolina, USA. Many students and university teachers are unfamiliar with the industry environment.
Includes bibliographical references and index.
Keywords: Biotechnology industries -- Case studies; Industries -- Service; Biotechnology industries